Implementation of Economic Rights Protection for Broadcast Right Holders of Football Matches Through the Consolidation of Compensation Claims in Criminal Cases Based on Law No. 28 of 2014 on Copyright and Article 98 of Law No. 8 of 1981 on Criminal Procedure - Noverina Alicia Putri; Muhamad Amirulloh; Aam Suryamah (Dinasti Research, 2024)
The development of information technology has influenced various sectors, including cinematography, which is protected by copyright law, especially in the context of broadcasting football matches. Despite copyright protection, many parties engage in unauthorized rebroadcasting, causing a breach of economic rights for the relevant rights holders. This research analyzes the legislative regulations protecting football broadcasting rights in Indonesia and the financial rights protection related to rebroadcasting. This research aims to understand the legal rules about football broadcasting rights and the safety of economic rights for broadcasting rights holders. A mixed legal study method combines normative and empirical legal research. The research results indicate that the Copyright Law provides adequate protection for the economic rights of football broadcasting rights holders. These exclusive rights are acquired by legal entities authorized to broadcast audiovisual works through radio media. Although criminal judgments cannot fully restore economic losses, mainly because they are penal, further steps are necessary to ensure compliance with these exclusive rights